SYSTEMATIC LITERATURE REVIEW: KETERAMPILAN BERPIKIR KREATIF MELALUI MODEL PROJECT BASED LEARNING - Suhartini Azis (Jurnal Pendidikan Sang Surya, 2024)
This study aims to explore creative thinking skills influenced by the Project-Based Learning (PjBL) model in the context of Biology and Science education, ranging from secondary schools to higher education institutions. The research employs the Systematic Literature Review (SLR) methodology. Relevant articles were sourced from Google Scholar and Garuda databases. A total of 170 articles published within the last three years (2021–2024) were identified using targeted search strategies and were subsequently filtered systematically according to the SLR framework, resulting in 16 valid articles that met the research criteria. The findings indicate that the implementation of the PjBL model positively impacts Biology and Science learning. The analyzed articles addressed the research questions regarding similarities, differences, and the extent of the model's influence on achieving educational goals. Key similarities were observed in terms of objectives, instruments, and outcomes, whereas differences emerged in themes or topics (subject matter), integration methods, types of research, subjects, data analysis techniques, and research output. From the reviewed literature, it can be concluded that creative thinking skills are significantly influenced by the application of the PjBL model across secondary and higher education levels, particularly in Biology and Science instruction.